2012
DOI: 10.1371/journal.pone.0029012
|View full text |Cite
|
Sign up to set email alerts
|

DNA Double-Strand Breaks Induced by Cavitational Mechanical Effects of Ultrasound in Cancer Cell Lines

Abstract: Ultrasonic technologies pervade the medical field: as a long established imaging modality in clinical diagnostics; and, with the emergence of targeted high intensity focused ultrasound, as a means of thermally ablating tumours. In parallel, the potential of [non-thermal] intermediate intensity ultrasound as a minimally invasive therapy is also being rigorously assessed. Here, induction of apoptosis in cancer cells has been observed, although definitive identification of the underlying mechanism has thus far re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(50 citation statements)
references
References 32 publications
2
48
0
Order By: Relevance
“…Additionally, cells receiving apoptotic signaling showed H2AX phosphorylation that is DNA-PK dependent [18], which was further corroborated in experiments using DNA-PK inhibitor and TNF-related apoptosis-inducing ligand (TRAIL) [18]. In line with previous research, we reported a reduction in the IRinduced γH2AX positive cell population in cells with an ATM specific inhibitor (KU55933) [12]. In the absence of ATM inhibitor, DNA-PK specific inhibitor (NU7026) did not affected the population of γH2AX positive cell, indicating that ATM is predominant kinase involved in H2AX phosphorylation after IR-exposure.…”
Section: Phosphorylation Of Histone H2ax In Cells Exposed To Ussupporting
confidence: 87%
See 3 more Smart Citations
“…Additionally, cells receiving apoptotic signaling showed H2AX phosphorylation that is DNA-PK dependent [18], which was further corroborated in experiments using DNA-PK inhibitor and TNF-related apoptosis-inducing ligand (TRAIL) [18]. In line with previous research, we reported a reduction in the IRinduced γH2AX positive cell population in cells with an ATM specific inhibitor (KU55933) [12]. In the absence of ATM inhibitor, DNA-PK specific inhibitor (NU7026) did not affected the population of γH2AX positive cell, indicating that ATM is predominant kinase involved in H2AX phosphorylation after IR-exposure.…”
Section: Phosphorylation Of Histone H2ax In Cells Exposed To Ussupporting
confidence: 87%
“…DNA-PK binds to the Ku70/Ku80 heterodimer that binds to and protects DNA ends from degradation, and contributes to DNA repair, such as nonhomologous end joining [27]. In addition to γH2AX foci formation, nuclear localization of phospho-ATM at Ser1981, phospho-DNA-PK at Ser2056/T2609 and phosphor-NBS1 at Ser343, which are activated forms of these proteins [28], were observed in US-treated cells [12]. Immunofluorescence analysis of γH2AX in U937, Jurkat, Molt-4, and HL-60 cells with US, IR (3 Gy), or TRAIL (0.1 mg/mL).…”
Section: Dna Repair Of Us Induced Dsbsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furusawa et al 103 found that Akt, a substrate of ataxia telangiectasia-mutated and DNA-dependent protein kinase (ATM/DNA-PK), was phosphorylated to the active form in U937 and Molt-4 cell lines without p53 when exposed to ultrasound. Furusawa et al 104 observed induction of apoptosis in cancer cells, which strongly supports involvement of a purely mechanical mechanism. These researchers were the first to demonstrate that exposure to ultrasound at even a moderate level of intensity has genotoxic potential because of its ability to damage DNA in cancer cell lines.…”
Section: Problemsmentioning
confidence: 81%